From Nature to the Lab: Establishing Drosophila Resources for Evolutionary Genetics - Faria, Vítor G.; Sucena, Élio (Frontiers in Ecology and Evolution, 2017)
In recent years important tools have been developed in Drosophila to capture with the greatest possible accuracy the variation found in nature. Efforts such as the Drosophila melanogaster Genetic Reference Panel (DGRP) or the Drosophila Synthetic Population Resource Panel (DSRP) allied to the advances in whole-genome sequencing and analysis have propelled to unprecedented level our capacity to dissect the genotype-phenotype map. However, several practical problems arise upstream of these analyses starting with the collection and identification of wild specimens. These problems are dealt with in different ways by each researcher generating solutions not necessarily compatible across laboratories. Here, we provide a systematic coverage of every phase of this process based on our experience, and suggest procedures to maximize and share the generated resources potentiating future applications. We propose a detailed pipeline to guide researchers from collection in the wild to the development of a large array of molecular and genetic resources. We designed a multiplex-PCR that distinguishes sister species D. melanogaster and D. simulans and is diagnostic of the presence/absence of Wolbachia infection. These procedures may extend to other cryptic species pairs and endosymbionts. We developed a standardized protocol to create, replicate and maintain isofemale lines and outbred populations. Finally, we explore the potential of outbred populations across several applications from experimental evolution, to introgression of transgenic constructs or mutant alleles, and genomic analyses. We hope to contribute to the success in developing Drosophila resources for evolutionary genetics studies and facilitate exchanges across laboratories based on a common set of procedures.